Assessing the Microbial Quality of Shrimp (Xiphonaeus kroyeri) and Mussels (Perna perna) Illegally Sold in the Vitória Region, Brazil, and Investigating the Antimicrobial Resistance of Escherichia coli Isolates - Link, Daniella Tosta; Viana, Gustavo Guimarães Fernandes; Siqueira, Lívia Pasolini; Ferraz, Carolina Magri; Rodrigues, Romário Alves [UNESP]; Mathias, Luis Antonio [UNESP]; Cardozo, Marita Vedovelli; Rossi, Gabriel Augusto Marques (MDPI, 2024)
The consumption of seafood is crucial for food security, but poor hygiene along the food production chain can result in low microbiological quality, posing significant risks for public health and seafood quality. Thus, this study aimed to assess the microbiological quality and antimicrobial sensitivity of E. coli from 69 samples of illegally marketed shrimp and mussels in the Vitória Region, Brazil. These foods exhibited poor microbiological quality due to high counts of mesophilic, psychrotrophic, and enterobacteria microorganisms. While this issue is widespread in this area, shrimp samples displayed higher microbial counts compared to mussels, and fresh mussels had elevated counts of enterobacteria compared to frozen ones. Among the 10 E. coli isolates, none carried the genes blaCTX-M-1, blaCTX-M-2, blaCTX-M-3, blaCTX-M-15, mcr-1, mcr-2, mcr-3, mcr-4, and tet, associated with antibiotic resistance. Phenotypical resistance to tetracycline and fosfomycin was not observed in any isolate, while only 20% demonstrated resistance to ciprofloxacin. Regarding ampicillin and amoxicillin with clavulanic acid, 60% of isolates were resistant, 10% showed intermediate susceptibility, and 30% were sensitive. One isolate was considered simultaneously resistant to β-lactams and quinolones, and none were conserved as ESBL producers. These findings highlight the inherent risks to local public health that arise from consuming improperly prepared seafood in this area.
Keywords: colistin; disk diffusion; enterobacteria; ESBL; mesophiles; psychrotrophs; seafood; shellfish; tetracycline; β-lactams